Musa velutina subsp. markkuana (Musaceae): a new subspecies from northeastern India - Sabu, Mamiyil; Joe, Alfred; Sreejith, Puravannoor E. (Phytotaxa, 2013)
A new subspecies of Musa velutina belonging to section Rhodochlamys from northeastern India is described and illustrated as Musa velutina subsp. markkuana. A detailed description, distribution, ecology, phenology and relevant taxonomic notes are provided.